STUDY OF PHYSICAL AND MENTAL WORKLOAD IN THE SMALL-SCALE TOFU INDUSTRY: AN ERGONOMIC PERSPECTIVE USING CARDIOVASCULAR LOAD AND NASA-TLX - Adi Nugroho; Amalia (RADJA PUBLIKA, 2025)
Human labor is still widely used by Micro, Small, and Medium-sized Enterprises (MSMEs) in Indonesia, especially those in the food processing sector, such as the tofu industry. Manual labor can place significant physical and mental demands on workers, especially when the number of workers is not proportional to the demands of the tasks assigned. Excessive workload in these aspects may result in fatigue and decreased productivity. This study aims to assess both physical and mental workloads in the production workstation by identifying workload intensity, including mental and physical aspects experienced by workers. The workloads with the greatest levels will be determined for more research and solutions. Cardiovascular Load (CVL) is used to measure physical workload, and National Aeronautical and Space Administration Task Load Index (NASA-TLX) is used to assess mental workload. These methods have identified varying degrees of physical and mental strain across different job roles. The results show that the cooking and filtering phases are key areas that demand particular focus. Workers in the cooking and filtering areas had respective CVL values of 30.60% and 30.24%, while the mental workloads assessed using the NASA-TLX reached 80.33 and 81.33.